Modelling of falling rock protection barriers. Issue 4 (December 2011) - Govoni, Laura; de Miranda, Stefano; Gentilini, Cristina; Gottardi, Guido; Ubertini, Francesco
Abstract : Falling rock protection barriers, flexible metallic structures conceived to intercept and stop falling blocks, are now widely used. Nonetheless, their complex behaviour has not been fully investigated yet and relevant design methods, based on full-scale testing of prototypes, in many circumstances may not be fully adequate. A programme of full-scale tests and finite-element analyses has considered three types of barrier subjected to the impact of blocks of kinetic energies ranging from 500 to 5000 kJ, in order to examine the highly non-linear response of these structures under dynamic conditions. Details of the experiments are herein described and a simple two-dimensional numerical model, devised on the basis of the tests, is presented. Retrospective simulation of the full-scale experiments shows the model reliability and applicability in such conditions, providing the essential basis for parametric analysis and preliminary design. A complete, full three-dimensional, finite-element analysis would eventually represent a more elaborate and effective design tool.